Fast ferroresonance suppression of coupling capacitor voltage transformers. - Graovac, M. (IEEE Transactions on power delivery)
This paper describes a procedure for fast suppression of the phenomenon of ferroresonance in coupling capacitor voltage transformers (CCVT) without major change in the CCVT design. It is shown that it is possible to adjust parameters of the secondary overvoltage protection and the filter circuit so that the ferroresonance can be cleared in a very short time interval. The study cases reported in this paper show that ferroresonance is effectively cleared within two cycles. An implementation of metal oxide varistors (MOV) as part of passive ferroresonance protection is also addressed. The Electromagnetic Transients Program (EMTP) is used for modeling transients and fine-tuning the ferroresonance suppressing circuit. The studies are conducted on the Trench TEHMP161A CCVT.